Children, Young people and Mobility as a Service: Opportunities and barriers for future mobility. (March 2020) - Casadó, Regina Gairal; Golightly, David; Laing, Karen; Palacin, Roberto; Todd, Liz
Abstract: The following paper examines the needs and perceptions of children and young people (age 8–18) towards Mobility as a Service (MaaS). MaaS offers a new paradigm in the access, planning and pricing of travel. To date, however, young people's views and needs have not been explicitly considered within this context. This is despite more general transport work demonstrating that young people have specific needs and perceptions that could influence their use of MaaS now, and their ongoing perceptions of MaaS across their life. Views of young people towards the MaaS concept were captured through workshops using Lego™. Thematic analysis identified specific considerations for young people's perceptions of MaaS around the experience of travel, travel choices, technology, safety, and status and identity. These results include barriers to acceptance and adoption of MaaS, but also reservations regarding the underpinning transport services. These results also demonstrate the importance of recognising young people as active agents in the use of transport rather than passive users, while sharing many of the concerns of adult users. Young people have a rich and complex voice that needs to be considered in the context of a digitalised 21st century transport service provision and understand young people as having agency around their travel choices. As such this paper fills a critical research gap in the MaaS literature. Highlights: Children and young people are key Mobility as a Service (MaaS) users. Children and young people have concerns not only to MaaS, but to underpinning transport modes. Children and young people have divergent needs and perceptions from a normative adult population. Children and young people have their own agency and voice that can be captured for MaaS design and deployment.